Effect of Disulfide Cyclization of Ultrashort Cationic Lipopeptides on Antimicrobial Activity and Cytotoxicity - Damian Neubauer (International Journal of Molecular Sciences, 2020)
Ultrashort cationic lipopeptides (USCLs) are considered to be a promising class of antimicrobials with high activity against a broad-spectrum of microorganisms. However, the majority of these compounds are characterized by significant toxicity toward human cells, which hinders their potential application. To overcome those limitations, several approaches have been advanced. One of these is disulfide cyclization that has been shown to improve drug-like characteristics of peptides. In this article the effect of disulfide cyclization of the polar head of N-palmitoylated USCLs on in vitro biological activity has been studied. Lipopeptides used in this study consisted of three or four basic amino acids (lysine and arginine) and cystine in a cyclic peptide. In general, disulfide cyclization of the lipopeptides resulted in peptides with reduced cytotoxicity. Disulfide-cyclized USCLs exhibited improved selectivity between Candida sp., Gram-positive strains and normal cells in contrast to their linear counterparts. Interactions between selected USCLs and membranes were studied by molecular dynamics simulations using a coarse-grained force field. Moreover, membrane permeabilization properties and kinetics were examined. Fluorescence and transmission electron microscopy revealed damage to Candida cell membrane and organelles. Concluding, USCLs are strong membrane disruptors and disulfide cyclization of polar head can have a beneficial effect on its in vitro selectivity between Candida sp. and normal human cells.